Social marketing: a commercial marketing strategy for understanding and improving health - Kumar, Mohan; Pathak, Vineet Kumar; Tripathi, Saparya (International Journal of Research in Medical Sciences, 2021)
Disease prevention and health promotion is now looking forward to newer innovative platforms to bring social change. Social marketing is a process that applies marketing principles and techniques to create, communicate, and deliver value in order to influence target audience behaviours that benefit society (public health, safety, the environment and communities) as well as the target audience. There are many challenges of marketing approach in India like financial cost, non-availability of audience data, difficulty in measuring marketing efforts, negative demand benefit to third party etc. These challenges can be dealt with 8 benchmark of social marketing which includes exchange, self-interest, behaviour change, competition, audience segmentation, consumer orientation, formative research and marketing mix (4 ‘P’s). Currently in India, condoms are social marketed under NACP-IV which can be extended to OCPs, Injectable contraceptives, ORS, Mosquito nets etc. For success of social marketing incorporation of consumers as partners into the planning process is must along with training of health professionals to enable them to imbue public health organizations with a marketing mind-set. Grantees should be given sufficient time and resources to conduct formative research, develop evidence-based marketing strategies, pretest program interventions, and monitor program activities.